Comments on "Dynamism of magnetohydrodynamic cross nanofluid with particulars of entropy generation and gyrotactic motile microorganisms". (April 2021) - Awad, M.M.
Abstract: Corrections to the units of magnetic field strength (B0 ) and electrical conductivity (σ) in Nomenclature are given so that the momentum equation is correct and the Hartman number (Ha ) is dimensionless. The similarity variable (η) depends only on r. From the equations of energy and concentration, temperature (T) and concentration (C and n) depend on r, z. In addition, the temperature θ(η) depends only on r while RHS depends on r, z. Hence, there is a discrepancy between LHS & RHS so that the equation of temperature is not valid. Also, the concentration φ(η) and ξ(η) depend only on r while RHS depends on r, z. Hence, there is a discrepancy between LHS & RHS so that the equations of concentration are not valid. Furthermore, a correct Be form is given.